Factors Influencing Knowledge and Acceptance of Nonavalent Human Papillomavirus Vaccine Among University Population in Southern China: A Cross-Sectional Study - Peiwan Fang; Haiyan Zheng; Li Liu; Jie Pan; Mianjia Chen; Xiaolin Yu; Miao Chen; Weicheng Yuan (Cancer Control)
Background Vaccine hesitancy among young Chinese remains a challenge, contributing to low vaccination rates for the nonavalent Human Papillomavirus (HPV) vaccine. This study evaluated the knowledge and acceptance of this vaccine among students at a southern Chinese university and identified factors influencing these outcomes. Methods This cross-sectional, anonymous questionnaire survey was conducted from April to November 2023 at a multi-campus university in southern China. The questionnaire was comprised of three sections: the first collected demographic data; the second evaluated students’ knowledge of the nonavalent HPV vaccine on a scale from 0 to 15, with cut-off points at 5 and 10 delineating low, medium, and high knowledge levels, respectively; the third section assessed vaccine acceptance on a scale from 8 to 40, using scores above the 50th percentile as the benchmark for positive acceptance. Results Among the participants, 18% demonstrated low-level, 40.20% medium-level, and 41.70% high-level knowledge of the nonavalent HPV vaccine. Notably, 71.95% of respondents showed positive acceptance, whereas 28.05% expressed negative acceptance. Male students and those with lower economic conditions (monthly living expenses below 1000 RMB, P = 0.004; 1000-1499 RMB, P = 0.012) exhibited lower knowledge levels. As for acceptance, female students and those with higher monthly living expenses (1000-1499 RMB, P = 0.007; 1500-1999 RMB, P = 0.002; over 2000 RMB, P = 0.002) demonstrated greater vaccine acceptance. A positive correlation was noted between the level of knowledge and vaccine acceptance (r s = 0.256, P < 0.001). Conclusions Gender and economic status are significantly associated with nonavalent HPV vaccine knowledge and acceptance among university students. These findings highlight the potential impact of targeted educational initiatives, especially for economically disadvantaged male students, in enhancing vaccine uptake rates.